Contributions to the National Status Report on Biological Invasions in South Africa - Wilson, John R.U.; Gaertner, Mirijam; Richardson, David M.; van Wilgen, Brian W. (African Biodiversity & Conservation, 2017)
South Africa has committed to producing a National Status Report on Biological Invasions by October 2017 and thereafter every three years. This will be the first status report at a national level specifically on biological invasions. As part of soliciting input, a workshop was held in May 2016 that led to this special issue of 19 papers in the journal Bothalia: African Biodiversity and Conservation. This editorial introduces the symposium, discusses the special issue and summarises how each contribution provides an estimate of ‘status’. Papers focus on key pathways, taxa, areas, and evaluations of interventions, specifically the movement of taxa between South Africa and neighbouring countries; the dispersal pathways of amphibians; a review of alien animals; a report on changes in the number and abundance of alien plants; in-depth reviews of the status of invasions for cacti, fishes, fungi and grasses; an assessment of the impact of widespread invasive plants on animals; reviews on invasions in municipalities, protected areas and sub-Antarctic Islands; assessments of the efficacy of biological control and other control programmes; and recommendations for how to deal with conflict species, to conduct scientific assessments and to improve risk assessments. The papers in this special issue confirm that South Africa is an excellent place to study invasions that can provide insights for understanding and managing invasions in other countries. Negative impacts seem to be largely precipitated by certain taxa (especially plants), whereas invasions by a number of other groups do not, yet, seem to have caused the widespread negative impacts felt in other countries. Although South Africa has effectively managed a few biological invasions (e.g. highly successful biological control of some invasive plants), the key challenge seems to be to establish and maintain a strong link between implementation, monitoring, reporting and planning.